2010
DOI: 10.1002/cbf.1648
|View full text |Cite
|
Sign up to set email alerts
|

Phytoglycoprotein (75 kDa) inhibits expression of interleukin‐1β stimulated by DEHP in human mast cells

Abstract: The purpose of this study is to investigate the inhibitory effect of a glycoprotein (CTB glycoprotein, 75 kDa) isolated from Cudrania tricuspidata Bureau (CTB) on the di-(2-ethylhexyl)phthalate (DEHP) induced expression of allergic-inflammation-related mediators in human mast cells. The changes on the levels of intracellular reactive oxygen species (ROS), mitogen-activated protein kinase (MAPK), transcription factor [nuclear factor (NF)-kappaB], and allergic inflammatory mediators [cyclooxygenase (COX)-2 and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Our results revealed that pretreatment with MEK1 inhibitor PD98059 (20 μM) or p38 inhibitor SB203580 (25 μM) significantly reduced DEHPinduced expression of ICAM-1 and IL-8, indicating that DEHP induction of ICAM-1 and IL-8 expression was mediated through ERK1/2 and p38 signaling pathways. We also found that the relative levels of phosphorylated ERK1/2 and p38 protein were significantly upregulated following DEHP treatment for as early as 15 min, which was consistent with previous findings [7]. This induction was effectively inhibited by pretreatment of curcumin and PD98059 which suggested that the anti-inflamma- tory activity of curcumin was related to the modulation of ERK1/2 and p38 MAPK activation in HUVECs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results revealed that pretreatment with MEK1 inhibitor PD98059 (20 μM) or p38 inhibitor SB203580 (25 μM) significantly reduced DEHPinduced expression of ICAM-1 and IL-8, indicating that DEHP induction of ICAM-1 and IL-8 expression was mediated through ERK1/2 and p38 signaling pathways. We also found that the relative levels of phosphorylated ERK1/2 and p38 protein were significantly upregulated following DEHP treatment for as early as 15 min, which was consistent with previous findings [7]. This induction was effectively inhibited by pretreatment of curcumin and PD98059 which suggested that the anti-inflamma- tory activity of curcumin was related to the modulation of ERK1/2 and p38 MAPK activation in HUVECs.…”
Section: Discussionsupporting
confidence: 92%
“…Increased indoor level of DEHP has been associated with an increased risk of admissions for allergic asthma and other airway diseases in children [5]. Studies have shown that DEHP has an adjuvant effect on allergen-induced immunoglobulin production through enhancing allergic-related inflammatory response including stimulation of the production of inflammatory mediators (IL-4, COX-2, TNF-alpha, and IL-8) in a variety of cell lines and in mice [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…In the present study, we demonstrated for the first time that apigenin flavonoid effectively attenuated DEHP-induced allergic inflammation by reduction of the expression of pro-inflammatory There were reports suggesting that phthalates including DEHP may adversely affect human immune functions, thereby enhancing the progress of allergic inflammatory disorders such as allergic asthma [23,24]. One possible reason is that phthalates have the potential to increase the expression of cytokines or chemokines in inflammatory cells [25]. DEHP was reported to cause an increase in the amount of IgG, which is associated with the development of allergic respiratory diseases [26].…”
Section: Discussionmentioning
confidence: 76%
“…A series of events related to the airway inflammation then took place, and vice versa (Nose, 2000;Manojkumar et al, 1998). Specifically, the intracellular GSH level in antigen-presenting cells influenced the Th1/Th2 cytokine response pattern, and more precisely, GSH depletion inhibited the Th1-associated cytokine production and/or favored the Th2 associated responses (Oh et al, 2010). Meanwhile, the increased MDA level in lung tissue could enhance the leucocyte chemotaxis and alter histamine release, thus perpetuating inflammation.…”
Section: Oxidative Stress and The Dehp-adjuvant Effectmentioning
confidence: 98%